ANALISIS TEGANGAN DAN REGANGAN PADA KAWAT STAINLESS STEEL 304 HASIL PERLAKUAN HARDENING DAN TEMPERING - Sekiwa; Suprapto, Agus; Tsamroh, Dewi Izzatus; Rusdijanto (Universitas Islam Malang, 2024)
Currently, the demand for materials, especially metals, is very significant. Iron and steel are inseparable basic needs. However, with diverse needs, the desired mechanical characteristics of a material also vary. These mechanical aspects include hardness, ductility, strength, and toughness. The use of stainless steel is increasing worldwide due to its superior characteristics. One of them is using stainless steel wire. This research aims to identify the tensile strength limit of 304 stainless steel wire with variations in hardening and tempering. The test results show that the unheat treated 304 stainless steel wire has a higher stress value than the heat treated one. The test results show that the stress value in the test object which has undergone heat treatment of hardening at a temperature of 820°C with a holding time of 30 minutes with water cooling and tempering at a temperature of 400°C with a holding time of 20, 30, 40 minutes with air cooling has decreased. This can be compared with raw or untreated specimens which have a stress value of 176.815 kg/mm2. For specimens that underwent the hardening heat treatment process, the stress value decreased to a value of 88.025 kg/mm2. Meanwhile, for test objects that underwent a tempering process, the stress also decreased compared to normal or untreated test objects with stress values ​​for 20 minutes of tempering 87,261 kg/mm2, 30 minutes of tempering 87,261 kg/mm2, and 40 minutes of tempering 87,006 kg/mm2.